2021
DOI: 10.3389/fphar.2020.630244
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Regulated the Homeostasis of Memory T Cell and Ameliorated Dextran Sulfate Sodium-Induced Experimental Colitis

Abstract: Immune memory is protective against reinvasion by pathogens in the homeostatic state, while immune memory disorders can cause autoimmune disease, including inflammatory bowel disease. Curcumin is a natural compound shown to be effective against human inflammatory bowel disease and experimental colitis, but the underlying mechanism is unclear. Here, experimental colitis was induced by dextran sulfate sodium (DSS) in this study. Significant changes in the percentages of naïve, central memory T (TCM), and effecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Mesalazine (batch number: 130407) was purchased from Sunflower Pharma (Jiamusi, China). e doses of curcumin and mesalazine were based on our previous study [18], in which curcumin was added to 1.5% sodium carboxymethylcellulose. e DSS + Cur group was orally administrated with curcumin (100 mg/kg/day) for 14 consecutive days, and the DSS+5-ASA group was orally administrated with mesalazine (300 mg/kg/day), and the Control and DSS groups were given an equal volume of saline, starting from day 8.…”
Section: Dss-induced Experimental Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…Mesalazine (batch number: 130407) was purchased from Sunflower Pharma (Jiamusi, China). e doses of curcumin and mesalazine were based on our previous study [18], in which curcumin was added to 1.5% sodium carboxymethylcellulose. e DSS + Cur group was orally administrated with curcumin (100 mg/kg/day) for 14 consecutive days, and the DSS+5-ASA group was orally administrated with mesalazine (300 mg/kg/day), and the Control and DSS groups were given an equal volume of saline, starting from day 8.…”
Section: Dss-induced Experimental Colitismentioning
confidence: 99%
“…e potential anti-inflammatory effects of curcumin have been extensively studied in various experimental models of IBD over the last decade, including free radical scavenging, antioxidant increase, myeloperoxidase, COX-1, COX-2, LOX, TNF-α, IFN-c, and iNOS inhibition, regulation of multiple signaling pathways, especially kinases (MAPK and ERK) and transcription factors NF-κB [16,17]. Zhong et al also reported that curcumin effectively alleviated DSS-induced colitis, closely related to the regulation of immune memory homeostasis of T cells [18]. However, the modulatory effect of curcumin on M1/M2 macrophages in colitis mice has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of blood glucose was higher than 16.7 mmol/L on both occasions (Figure S2a), the DB mice were included in the subsequent experiments. Based on our previous study (Zhong et al, 2020; Zhong et al, 2021), DB mice were given 3% (w/v) DSS solution ad libitum and showed typical clinical symptoms of colitis starting from day 4 of the experiment, with significant weight loss (Figure S2b), anal blood (Figure S2c), generalized tremors and bradycardia, and all died on day 9 (Figure S2d), and post‐mortem examination revealed massive colonic bleeding (Figure S2e). This suggests that diabetes increases susceptibility to colitis in mice and is closely associated with deletion of the leptin receptor gene.…”
Section: Resultsmentioning
confidence: 99%
“…Before administration, Cur was dissolved in 1.5% (w/v) sodium carboxymethylcellulose (CMC) solution at a dose of 100 mg/kg (purity >95% by HPLC) (Zhong et al, 2020; Zhong et al, 2021). Throughout the experiment, mice in the DSS + Cur and Con+Cur groups were orally administered with 100 mg/kg/day Cur and for 21 consecutive days, and mice in the DSS and Control groups were treated with equal volume of saline.…”
Section: Methodsmentioning
confidence: 99%
“…However, its mechanism is unclear. El-Mahdy and his workmates reported that mesalazine can enhance anti-inflammatory effects to attenuate progression of oxazolone-induced colitis by restoring IL-10 and ZO-1 levels and limiting IL-6/STAT-3 trans-signaling [ 30 , 31 ]. Maybe, these supplied a possible effect to regulate memory T cells in the process of mesalazine treated mice colitis.…”
Section: Discussionmentioning
confidence: 99%